A rede de saúde mental infantojuvenil de Fortaleza: costuras e arremedos entre história, clínica e política - Maciel, Morena Simonetti Gomes (2023)
The history of child and adolescent mental health services in Brazil is marked by a delayed approach, which has had reverberations in the practices of caring for children and adolescents over the years. This research aims to provide a situational analysis of the development and implementation of a network for child and adolescent mental health in Fortaleza, Brazil. Initially, the study provides a critical discussion of the history and public policies in the field of mental health for children and adolescents. The first chapter offers an overview of different historical and political moments and a critical discussion of practices focused on children and adolescents based on legal and institutional frameworks that have emerged in different historical periods in Brazil. In the second chapter, the history of mental health in Ceará is examined, and the way in which the child and adolescent mental health network in Fortaleza has developed over the years is discussed. Finally, the third chapter presents a critical analysis of the child and adolescent mental health network in Fortaleza based on challenges identified by health professionals, using a qualitative exploratory research approach. The study offers insights into the development of mental health services for children and adolescents in Brazil, with a focus on the challenges faced in their implementation. For this reason the complexity of mental health care for children and adolescents, it is concluded that in addition to the extension of specialized services for this population, it is necessary to produce policies and ways of working, which guarantee an intersectoral work and in a network, to deal with a historically marginalized population. And it is in this sense that history, clinical practice and politics intertwine to promote other forms of care for these subjects.